Load-Dependent Increases in Delay-Period Alpha-Band Power Track the Gating of Task-Irrelevant Inputs to Working Memory - Heinz, Andrew J.; Johnson, Jeffrey S. (Frontiers in Human Neuroscience, 2017)
Studies exploring the role of neural oscillations in cognition have revealed sustained increases in alpha-band power during the delay period of verbal and visual working memory (VWM) tasks. There have been various proposals regarding the functional significance of such increases, including the inhibition of task-irrelevant cortical areas as well as the active retention of information in VWM. The present study examines the role of delay-period alpha-band power in mediating the effects of interference arising from on-going visual processing during a concurrent VWM task. Specifically, we reasoned that, if set-size dependent increases in alpha-band power represent the gating out of on-going task-irrelevant visual inputs, they should be predictive with respect to some modulation in visual evoked potentials resulting from a task-irrelevant delay period probe stimulus. In order to investigate this possibility, we recorded the electroencephalogram while subjects performed a change detection task requiring the retention of two or four novel shapes. On a portion of trials, a novel, task-irrelevant bilateral checkerboard probe was presented mid-way through the delay. Analyses focused on examining correlations between set-size dependent increases in alpha-band power and changes in the magnitude of the P1, N1 and P3a components of the probe-evoked response and how such increases might be related to behavior. Results revealed that increased delay-period alpha-band power was associated with changes in the amplitude of the N1 and P3a event-related potential (ERP) components, and with load-dependent changes in capacity when the probe was presented during the delay. We conclude that load-dependent increases in alpha-band power likely play a role in supporting short-term retention by gating task-irrelevant sensory inputs and suppressing potential sources of disruptive interference.